1977
DOI: 10.1139/v77-288
|View full text |Cite
|
Sign up to set email alerts
|

Electric field perturbed electron tunnelling in nonpolar organic glasses

Abstract: A. J. DOHENY and A. C. ALBRECHT. Can. J. Chem. 55,2065Chem. 55, (1977. Isothermoluminescence (ITL) and electrophotoluminescence (EPL) resulting from electroncation recombination are measured in a 2-methylpentane-methylcyclohexane glass. The ITL is more characteristic of quantum-mechanical tunnelling and the EPL signal is markedly stronger in this new glass than previous measurements in 3-methylpentane. Quantum-mechanical tunnelling theory is used to predict recombination rates of electrons in the potential fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Theoretical calculation where the distribution was taken into account was successful in the explanation of the data of electrophotoluminescence resulting from charge recombination in the presence of external electric field, though comparison between the Coulombic and square-barrier models was not made. 31 The present results provide poor materials for the discussion of the Franck-Condon factor. The theories predict that the Franck-Condon factor increases first with the free-energy difference -AG to a maximum, -AGm, and then decreases, and that -AGm is governed by vibrational properties of a super molecule consisting of donor, acceptor, and solvent molecules.13 '15 The values of -AG for electron transfer to matrix holes from propylamine and triethylamine are estimated crudely at 1.8 and 3.1 eV, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…Theoretical calculation where the distribution was taken into account was successful in the explanation of the data of electrophotoluminescence resulting from charge recombination in the presence of external electric field, though comparison between the Coulombic and square-barrier models was not made. 31 The present results provide poor materials for the discussion of the Franck-Condon factor. The theories predict that the Franck-Condon factor increases first with the free-energy difference -AG to a maximum, -AGm, and then decreases, and that -AGm is governed by vibrational properties of a super molecule consisting of donor, acceptor, and solvent molecules.13 '15 The values of -AG for electron transfer to matrix holes from propylamine and triethylamine are estimated crudely at 1.8 and 3.1 eV, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…9.5 M LiCl glasses. Doheny and Albrecht [15], and Tachiya and Mozumder [16] discussed the relation between the m value and the distribution of trapped electrons using the tunneling kinetics. However, it seems to be unreasonable to analyze the m value by the pure tunneling mechanism because of the involvement of the redistribution of trapped electrons between deep-and shallow-traps in the RP decay process.…”
Section: Resultsmentioning
confidence: 99%
“…Three main processes which are perturbed by the applied electric field are probably as follows: (1) the recombination process in which the recombination time, consequently the escape probability, depends upon the strength of the electric field and the angle between the direction joining the electron to the positive ion and that of the field; (2) the nonradiative transition process for electrons from a delocalized state to a localized state where the transition is a consequence of an electron-phonon coupling interaction; and (3) a transfer or detrapping process from a localized state to a delocalized state or another localized state by hopping or tunneling. 11 Kato et al 8 showed that the increase in the yield of e80f, e.g., ODe/ODq 1.06 for E = 50 kV cm-1, can be theoretically predicted by assuming that the electric field mainly perturbs process 1. They also comment that whatever the forms of the initial distribution function of thermalized electrons are, the calculated yield of eaof is always larger in the presence of an electric field than in ©…”
Section: Resultsmentioning
confidence: 99%
“…Reagent grade ethanol was filled between the mylar films. Uncracked ethanol glass was made at 77 K. A Spellman dc power supply was used to apply a high voltage of 11 kV between the electrodes during y irradiation. The electric field strength inside the sample was estimated to be 50 kV cm"1.10 7 irradiation was carried out at 77 and 4 K at a 0022-3654/79/2083-0822S01.00/0 dose rate of 0.48 Mrd h"1 to a dose of 0.16 Mrd.…”
Section: Methodsmentioning
confidence: 99%